DISTRIBUSI MAST CELL PADA MESENTERIUM TIKUS - N Ibrahim, Mohamad; Widjajanto, Edi; Rosita, Rita (Fakultas Kedokteran Universitas Brawijaya, 2008)
Mast cell are derived from haematopoietic progenitors in the bonemarrow. Developing mast cell subsequently migrate to peripheral tissues, such as the skin, mucosa and air way, where they terminate their differentiation under the influence of factors in the tissue micro-enviroment. This study aimed to know distribution and strucutre of mast cell on rat mesentery. The mesentery was stained with a 1 % safranine solution or toluidine blue on the a pepared slide. The prepared slides were immediately viewed by a observer through a microscope. The result showed that mast cells stained with safranine or toluidine blue were closely associated with postcapillary in the rat mesentery. Keywords : mast cell, mesentery